Understanding the influence of carbon nanotubes on the flow behavior of liquid crystalline hydroxypropylcellulose: a Rheo-NMR study - Echeverria Zabala, Coro (2020)
Hydroxypropyl celulose (HPC) is na importante celulose derivative that has been widely studied due to its water solubility, biocompatibility and biodegradability, but even more significant due to its ability to form liquid crystalline phases. HPC is able to form, under certain conditions, chiral nematic (cholesteric) structures in water solutions. Previous work confirmed that films prepared from liquid crystalline HPC/water solutions (LC-HPC) gave rise to anisotropic networks, with similar mechanical and optical characteristics of Liquid Crystalline Elastomers (LCE), capable to respond to humidity. It was also demonstrated that the incorporation of carbon nanotubes (CNTs) significantly improved the actuator responsiveness. In the work presented herein, we investigate how the incorporation of carbon nanotubes affects the flow behavior o fLC-HPC solutions, and thus the structure-properties relationship, through a detailed Rheo-NMR study. As observed from the results, when shearing the samples, the degree of order reached (maximum quadrupolar peak splitting) by LC-HPC solutions increases with CNT content. Regarding the subsequente relaxation process, only the incorporation of 0.01 wt% of CNTs (lowest content) contributes to a faster recovery of cholesteric structure.